Phytochemicals and biological activities of Elaeocarpus floribundus Blume, Barringtonia conoidea Griff and Fibraurea tinctoria Lour - Umar, Rahayu Utami (2012)
Phytochemicals and biological activity studies on three medicinal plants, Elaeocarpus floribundus Blume, Barringtonia conoidea Griff and Fibraurea tinctoria Lour were carried out. The chemical constituents of these plants were isolated using chromatographic methods, whilst the structure of the compounds were elucidated by using spectroscopic methods including infrared (IR), nuclear magnetic resonance (1H, 13C and 2D NMR), mass spectrometry (MS) and by comparison with previous data. Total phenolic content of methanolic extracts of plants was determined by colorimetric method using Folin-Ciocalteu reagent. Extracts and selected isolated compounds were subjected to biological activity studies of antimicrobial, antioxidant and cytotoxic activity. The isolation work on the leaves of Elaeocarpus floribundus has yielded triterpenoids, friedelin (38) and epifriedelinol (39). Mixture of α- (41) and β-amyrin (42) were isolated from leaves and stem bark of Barringtonia conoidea. This is a first report on the phytochemical study of Elaeocarpus floribundus and Barringtonia conoidea. While furanolactone diterpene, clerodanine (43), an ecdysteroid, 20- hydroxyecdysone (37) and an isoquinoline alkaloid, berberine (30) were obtained from the whole part of Fibraurea tinctoria. In addition, β-sitosterol (40) was isolated from these three plant species. In this present study, all methanolic extracts of plants showed significant amount of phenolic content. The methanolic extract of leaves of Elaeocarpus floribundus exhibited the highest value of 503.08±16.71 mg GAE/g DW. In the screening of antimicrobial activities, extracts of leaves and stem bark of Elaeocarpus floribundus and Barringtonia conoidea were either possessed weak activity or inactive against gram positive and negative bacterial strains. Extracts of Fibraurea tinctoria were found to be inactive towards the bacterial strains. Similarly, none of extracts of the plants gave inhibition activity towards fungal strains Candida albicans, Aspergillus ochraceaus and Saccharomyces cerevisiae. Antioxidant activity assay of extracts and isolated compounds have been conducted using DPPH free radical scavenging method. Only polar extracts of leaves and stem bark of Elaeocarpus floribundus as well as methanol extract of Fibraurea tinctoria afforded potential antioxidant activity. Clerodanine (43) was the only isolated compound that gave significant activity with IC50 value of 20.81±0.02 μg/ml. While, the others extracts as well as isolated compounds were found either to be weak or inactive. As for the cytotoxic assay, extracts and selected isolated compounds were tested using microculture tetrazolium (MTT) assay against human T4-lymphoblastoid cell (CEM-SS) and human cervical cancer cell (HeLa). The results showed that chloroform extract of leaves of Elaeocarpus floribundus and methanol extract of Fibraurea tinctoria gave significant activity against CEM-SS cells with IC50 values of 25.6±0.06 and 16.13±0.04 μg/ml, respectively. Ethyl acetate extract of stem bark and chloroform extract of leaves of Barringtonia conoidea exhibited promising activity towards HeLa cells with IC50 values of 13.5±0.16 and 28.1±0.01 μg/ml, respectively. Compounds 38, 39, 43 and mixture of 41 & 42 showed significant cytotoxic activity against the two cancer cells, with compound 38 gave the strongest activity with IC50 value of 3.54±0.30 μg/ml towards HeLa cells. Compound 43 was also found to be active against the two cancer cells with IC50 values of 12.49±0.10 μg/ml (CEM-SS) and 9.37±0.36 μg/ml (HeLa). This is the first study conducted on the cytotoxic activity of compound 43.